2011
DOI: 10.4097/kjae.2011.60.5.339
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on the usefulness of the Glidescope or Macintosh laryngoscope when intubating normal airways

Abstract: BackgroundThe Glidescope Videolaryngoscope (GVL) is a newly developed video laryngoscope. It offers a significantly improved laryngeal view and facilitates endotracheal intubation in difficult airways, but it is controversial in that it offers an improved laryngeal view in normal airways as well. And the price of GVL is expensive. We hypothesized that intubation carried out by fully experienced anesthesiologists using the GVL with appropriate pre-anesthetic preparations offers an improved laryngeal view and sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…17 Despite significant increase in percentage of visible glottic opening with Glidescope (P < 0.05), Choi GS et al did not find any difference in the time required for a successful tracheal intubation when compared with the Macintosh laryngoscope. 18 Similar finding for intubation time was observed in many other studies using KingVision video laryngoscope, Airtraq and Glidescope when all these were compared with Macintosh laryngoscope. 5,12,19 Unlike these studies, Castillo-Monzón CG et al and Dhonneur G et al found shorter intubation time with Airtraq when compared with Macintosh laryngoscope.…”
Section: Discussionsupporting
confidence: 87%
“…17 Despite significant increase in percentage of visible glottic opening with Glidescope (P < 0.05), Choi GS et al did not find any difference in the time required for a successful tracheal intubation when compared with the Macintosh laryngoscope. 18 Similar finding for intubation time was observed in many other studies using KingVision video laryngoscope, Airtraq and Glidescope when all these were compared with Macintosh laryngoscope. 5,12,19 Unlike these studies, Castillo-Monzón CG et al and Dhonneur G et al found shorter intubation time with Airtraq when compared with Macintosh laryngoscope.…”
Section: Discussionsupporting
confidence: 87%
“…Numerous studies have previously reported an improvement in CL grading. Some of these studies have been done in predicted or simulated difficult airways[ 13 14 15 16 ] while others in general patient population and normal airways[ 8 9 16 17 18 ] and findings of the present study further confirms and extends this evidence.…”
Section: Discussionsupporting
confidence: 87%
“…A light source and a digital video camera are positioned at the tip of the blade so that pictures of the glottis and vocal cords can be displayed on a monitor. Standard tracheal tubes can be inserted into the trachea more precisely, causing less tissue damage [1]. Compared with the direct Macintosh laryngoscope, the GlideScope videolaryngoscope has been reported to shorten intubation time and improve the success rate of the first attempt at intubation in normal and in difficult airways [2–4].…”
mentioning
confidence: 99%